CERVICAL SQUAMOUS EPITHELIUM LESIONS ASSOCIATED WITH HUMAN PAPILLOMAVIRUS INFECTION - V. A. Еrshov (Sankt-Peterburg : NIIÈM imeni Pastera, 2014)
Abstract. The cytological evidence of cervical squamous epithelium lesions associated with HPV infection was identified as the presence of koilocytes in 16% of patients and atypical multicore cells with core and/or cytoplasm dystrophy of para-basal layer cells in 46%. The high grade squamous intraepithelial lesions were associated with the presence of HPV 16 mostly in combination with other high risk HPV genotypes.